Dostoevsky and the lacerated foreshortenings of the soul - Esteban Ortega, Joaquín (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
It could be said that in enlightened modernity the tragic ceases to be expressed publicly in a specific cultural genre and is led to the intimate spaces that the autonomous individual finds in the novel. The resistance of the tragic becomes a tension with the philosophical in the new personal place of literature. Dostoevsky becomes paradigm and destiny thereof. This article remarks the philosophical ability of his literature to make transparent the abysses of the human soul. We will see how, only by admitting the wounds of existence, the truth can be told, even if life is at stake. In his narrative energy we find the contradictory force that animates existence within the framework of nihilism and compassion. Can his tragic philosophy make us free from the current dangerous and dogmatic drifts of idealism?